A 9month-old-boy with atypical hemophagocytic lymphohistiocytosis - Monia Ouederni; MONIA BEN KHALED; Samia Rekaya; Ilhem Ben Fraj; Fethi Mellouli; Mohamed Bejaoui (Mediterranean Journal of Hematology and Infectious Diseases, 2017)
Hemophagocytic lymphohistiocytosis is a life-threatening hyperinflammation caused by uncontrolled proliferation of activated lymphocytes and histiocytes. Often, Hemophagocytic lymphohistiocytosis is an acquired syndrome. We report a case of a 9 month-old-boy presented with hepatosplenomegaly, severe anemia requiring repeated transfusions, thrombocytopenia, hypertriglyceridemia and very high hyperferritinemia. These clinical features of Hemophagocytic lymphohistiocytosis prompted a wide infectious and auto-immune request to be performed.  After a wide diagnostic workup, he was referred to the immune hematologic unit, for hemophagocytic lymphohistiocytosis  suspicion with unknown cause.